Routledge Handbook on the Sciences in Islamicate Societies Practices from the 2nd/8th to the 13th/19th Centuries - Brentjes, Sonja; Barker, Peter; Brentjes, Rana (Taylor & Francis, 2022)
History of Science and Technology, Intellectual History, Medieval History, Religious History, Social and Cultural History, World/International History